Features of the surgical treatment of the femoral head fractures (Pipkin) - K. S. Polyushkin; A. V. Shevchenko (Кубанский научный медицинский вестник, 2015)
In our clinic from 2011 to 2013 12 patients with femoral head fructures (Pipkin) were treated. 2 patients with the Pipkin I type were conservatively treated. The others were operated. For successful surgical treatment of the femoral head fractures, you should use only an open anatomical reduction and stable fixation in the shortest possible time after trauma. In cases of Pipkin I and II types was used less traumatic anterior approach to the hip joint, and posterior approach at the IV type of a femoral head fracture. When the femoral neck and head were fractured with the prescription of more than a day you should think about the primary hip arthroplasty.There were not intraoperative and early postoperative complications at our patients.